(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This chapter comprehensively analyzes the theoretical foundations, practical significance, and effectiveness of utilizing modern pedagogical technologies to enhance lesson quality. The study examines technologies such as blended learning, flipped classroom, gamification, project-based learning, personalized, and adaptive education. It critically evaluates the impact of these technologies on student engagement, motivation, and achievement, as well as teacher competencies, implementation challenges, and ethical considerations. Recommendations for improving the educational process are provided, based on contemporary pedagogical approaches including constructivism and Shulman’s Pedagogical Content Knowledge (PCK) theory.